If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-19=u/3-23
We move all terms to the left:
-19-(u/3-23)=0
We get rid of parentheses
-u/3+23-19=0
We multiply all the terms by the denominator
-u+23*3-19*3=0
We add all the numbers together, and all the variables
-1u+12=0
We move all terms containing u to the left, all other terms to the right
-u=-12
u=-12/-1
u=+12
| 57.5=20+x | | 7(u+2)=77 | | 57.5=85-y | | 3-3x-3+2x=4x+3x | | 3.6g=21,6 | | 23=q/4—16 | | 85-y=20+y | | y=25+25 | | 5x/3+5=-1/3+x | | 4b+5=1+5b4+b+5=1+5b | | 35+x=85-x | | 4b+5=1+5b4,b+5=1+5,bb | | 9(h-79)=90 | | 77x=89-2x | | 85-x=35+x | | 3y-36=45 | | n/2+36=46 | | 17=3y+y-1 | | X+2/14=1/7+x-1/9 | | 6(6c-2)+8(1-5c)=-2 | | 15-3g=6 | | 26+.35p=75 | | -3(1+z)–17=-8 | | 4(7+4x)=42-6x | | -94=-58+-p | | 12=r-1 | | 4-(7n)=(3n)-12 | | -3s+34=-8 | | 2/7g=-10 | | X+8/18=8/9+x-9/8 | | 21-3r=12 | | 9+(2n)=(3n)-2 |